Identificação dos componentes citotóxicos do veneno da serpente Bothrops atrox e caracterização dos efeitos celulares e metabólicos induzidos pela proteína recombinante L-aminoácido oxidase (LAAO) - Letícia Lopes de Souza (2022)
Snakebites are a global public health problem, and in Brazil, more than 20 thousand cases occur annually. The North region accounts for more than 40% of accidents and, from an epidemiological perspective, Bothrops atrox snake is the most important in the Amazon rainforest of South America. Envenomation by this snake causes systemic and local symptoms triggered by the synergistic action of the toxins present in the venom. Treatment consists of antivenoms use, which act by neutralizing the toxins actions. However, antivenoms do not always neutralize local damage efficiently and, in these cases, the skin is the main organ affected. Therefore, the first objective of the project was to evaluate the effect of B. atrox venom on keratinocytes, the main cell type in the skin. Metalloproteases and L-amino acid oxidases were identified as the main proteins responsible for the cytotoxicity. Next, LAAO was selected for the characterization of its cellular and metabolic effects. It was produced in a recombinant form (rLAAO) and showed cytotoxicity against keratinocytes and human endothelial cells, affecting important cell adhesion proteins. On the other hand, the mutated version of LAAO (rLAAOR90A), which does not present catalytic activity, demonstrated significantly reduced effects, indicating that those actions are catalysis dependent. A high throughput approach using omics methodologies was employed to evaluate the effects of rLAAO on metabolism. The proteome, amino acids and biogenic amines and the lipidome of treated human cells were analysed. Results demonstrate that in the presence of LAAO, several molecules and cellular processes are regulated. Among them, DNA methylation and repair, cell adhesion, autophagy, as well as antioxidant and lipid catabolism pathways are affected. These data present an innovative and promising approach in the Toxinology field, which could be used to identify molecules involved during the envenomation and could be used as molecular targets. This contributes to the characterization of cellular and metabolic mechanisms that occur during envenomation and for the development of therapies focused on these mechanisms, helping to the treatment of local effects caused by bothropic venoms.